Pengaruh Disiplin Kerja, Pelatihan Keterampilan, dan Kerjasama Tim Terhadap Kinerja Pegawai di Sektor Penanggulangan Kebakaran dan Penyelamatan Kecamatan Pesanggrahan Jakarta - Feri Hamdantika; Anita Maulina (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Employee performance is the most important part in the development and survival of an organization. An organization will survive and continue to develop if the organization's goals are achieved. This research discusses and analyzes the influence of work discipline, skills training, and teamwork on employee performance in the Fire Management and Rescue Sector, Pesanggrahan District. The research method used is a quantitative method by distributing questionnaires with a sample size of 48 respondents from a population of 48 people. Based on the results of research using multiple regression analysis with the help of SPSS 26.0, it shows that work discipline has a positive and significant influence with a coefficient of determination (R Square) of 0.720 (72.0%) on employee performance, skills training has a positive and significant influence with coefficient of determination (R Square) of 0.999 (99.9%) on employee performance. Teamwork has a positive and significant influence with a coefficient of determination (R Square) of 0.790 (79.0%) on employee performance. The independent variables work discipline, skills training and teamwork were jointly tested using the F test, proving that they have a positive and significant influence with an F value of 10,798.209 on employee performance and the magnitude of the influence is seen from the value and with a coefficient of determination (R Square) value of 0.999 (99.9%).